First report on antioxidant and antimicrobial activities of essential oil of Persea americana from Algeria - AIT MIMOUNE, NOUARA (Journal of the Chilean Chemical Society, 2024)
The present investigation describes the chemical profile and biological activities of Persea americana essential oil (EO) isolated by hydrodistillation. The chemical composition was determined using Gas Chromatography-Mass Spectrometry (GC–MS). The main compounds found were represented by estragole (65.5%) and methyleugenol (10.94%). The antibacterial activity was evaluated against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae. Results revealed the effectiveness of the essential oil on both Gram-positive and Gram-negative bacteria. The screening of antifungal activity was performed using poisoned food and broth-microdilution assays. P. americana EO was capable of inhibiting the mycelial growth of all tested fungi, with Cladosporium sp. and Altenaria sp. being the most sensitive species. The DPPH test performed to determine the antioxidant activity showed a low IC50 value of 0.22 mg/mL. Overall, P. americana EO proved to be an effective antimicrobial and antioxidant agent, that could be used as a natural perspective to control foodborne pathogens and lipid peroxydation.